Pencegahan Stunting melalui Peningkatan Kesadaran Hak- Hak Reproduksi Perempuan Usia Pra Nikah di Panti Asuhan 'Aisyiyah Kota Payakumbuh - Asmaret, Desi; Halim, Syaflin; Prima, Rezi; Anggraini, Yuliza; Alvira, Selsa; Irfianda, Irfianda (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The children of the 'Aisyiyah Payakumbuh Orphanage, in their teens, have never been equipped with knowledge about women's reproductive rights. Therefore, it is necessary to be given knowledge about the independence of reproductive rights to break the chain of stunting. This service aims to build awareness and empower orphanage children through the process of increasing awareness of reproductive rights that bring change (transformative) that is independent in maintaining their reproductive health in making the right decisions that are free from discrimination, coercion and violence. In particular, this PKM received a DRTPM grant from the Ministry of Education, Culture, Research and Technology of the Directorate General of Higher Education, Research, and Technology in the field of Community Empowerment in order to realize the Sustainable Development Goals (SDGs), namely a healthy and prosperous life by building partnerships. This service uses socialization, training and continuous cooperation methods to produce outputs in the form of articles in sinta indexed journals, recognition of student credits, publications in electronic mass media, uploading videos of activities on the university's youtube and PKM posters in HaKi kan as well as Cooperation and MoA agreements with the Family Law Study Program and the Faculty of Islamic Religion, University of Muhammadiyah West Sumatra for sustainable programs.